2012
DOI: 10.3190/jgeosci.118
|View full text |Cite
|
Sign up to set email alerts
|

Petrology of the Late Cretaceous peralkaline rhyolites (pantellerite and comendite) from Lake Chad, Central Africa

Abstract: Late Cretaceous peralkaline rhyolites (69.4 ± 0.4 Ma -2σ analytical, 1.9 Ma full external uncertainty, 40 Ar/ 39Ar sanidine single crystal laser dating) from Lake Chad are the oldest lavas of the "Cameroon Hot Line". These lavas (pantellerite and comendite), consisting of quartz ± alkali feldspar ± fluoro-arfvedsonite ± augite-hedenbergite ± aegirine ± fayalite (Fa 97-99 ) and ilmenite, are characterized by a progressive increase in the total REE contents and the magnitude of the negative Eu anomaly owing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 24 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…In this study we dated two units within a well-logged rock sequence in order to place the ages within a lithostratigraphic bracket. Kamgang et al (2007Kamgang et al ( , 2008Kamgang et al ( , 2010Kamgang et al ( , 2013, Wandji et al (2008), Mbowou et al (2012), Itiga et al (2013). ages presented here are also more precise, constraining the ages for the two felsic rock units in the Sabga area at ~23.0 ± 0.3 Ma. This age is interpreted as the time of crystallization of the zircons and corresponds broadly to the emplacement ages of the rhyolitic rocks.…”
Section: Age Variation Of Volcanic Rocks Along the Cvlsupporting
confidence: 54%
See 1 more Smart Citation
“…In this study we dated two units within a well-logged rock sequence in order to place the ages within a lithostratigraphic bracket. Kamgang et al (2007Kamgang et al ( , 2008Kamgang et al ( , 2010Kamgang et al ( , 2013, Wandji et al (2008), Mbowou et al (2012), Itiga et al (2013). ages presented here are also more precise, constraining the ages for the two felsic rock units in the Sabga area at ~23.0 ± 0.3 Ma. This age is interpreted as the time of crystallization of the zircons and corresponds broadly to the emplacement ages of the rhyolitic rocks.…”
Section: Age Variation Of Volcanic Rocks Along the Cvlsupporting
confidence: 54%
“…Dunlop and Fitton 1979;Marzoli et al 1999Marzoli et al , 2000Ngounouno et al 2003;Aka et al 2004;Fosso et al 2005;Njilah et al 2007;Wandji et al 2008;Kamgang et al 2010Kamgang et al , 2013Mbowou et al 2012;Itiga et al 2013;Tchuimegnie Ngongang et al 2015). These works have shown that the ages along the CVL range from 69.4 ± 0.4 Ma to Present (Fig.…”
Section: Age Variation Of Volcanic Rocks Along the Cvlmentioning
confidence: 99%
“…The Tchabal Mbabo basement consists of granitic and gnessic rocks, rising up to 2100 m. Those rocks are probably Pan African in age, as shown by those described at Méiganga (Ganwa et al 2008) and northern Ngaoundéré, with ages of 610-652±54 Ma and 926±12 Ma (Tchameni et al 2006), which place them within the Central Pan-African Chain (CPAC). CVL is composed of volcanic centres and anorogenic complexes with volcanic rocks, forming a chain of Tertiary to recent lavas (Déruelle et al 1991;Kamden et al 2002;Kamgang et al 2010;Mbowou et al 2012). Continental magmas evolve towards peralkaline rhyolite lavas, whereas those in the oceanic sector evolve towards phonolites (Fitton 1987).…”
Section: Geological Settingmentioning
confidence: 99%
“…Then, the lack of age progression along the CVL magmatism renders the age determination of each volcano of the line indispensable to modelize the entire CVL. Moreover, the AP geochronology (Gouhier et al 1974;Temdjim et al 2004; Nkouandou et al 2008 ;Fagny et al 2012) evidenced that these volcanoes are relatively more recent (11 Ma to recent) than those of the CVL (up to 70 Ma to recent, Mbowou et al 2012). Thus, whether the AP magmatism belongs to CVL, as proposed in the Y-shaped model for the whole CVL (Fitton, 1980(Fitton, , 1983, though largely debated (Gouhier et al 1974; Aka et al 2004Aka et al , 2009Nkouandou et al 2010), remains questionable and requires many more age determinations.…”
Section: Introductionmentioning
confidence: 99%
“…and Hadjer Hidjer (283 m a.s.l. ), with particular rhyolitic compositions (pantellerite and comendite) are located to the SE of Lake Chad (Mbowou et al 2012).…”
Section: Geological Settingmentioning
confidence: 99%